Magnetic field effect on laser-induced breakdown spectroscopy and surface modifications of germanium at various fluences. (10th February 2017) - Iftikhar, H.; Bashir, S.; Dawood, A.; Akram, M.; Hayat, A.; Mahmood, K.; Zaheer, A.; Amin, S.; Murtaza, F.
Abstract: The effect of the transverse magnetic field on laser-induced breakdown spectroscopy and surface modifications of germanium (Ge) has been investigated at various fluences. Ge targets were exposed to Nd: YAG laser pulses (1064 nm, 10 ns, 1 Hz) at different fluences ranging from 3 to 25.6 J/cm 2 to generate Ge plasma under argon environment at a pressure of 50 Torr. The magnetic field of strength 0.45 Tesla perpendicular to the direction of plasma expansion was employed by using two permanent magnets. The emission spectra of laser-induced Ge plasma was detected by the laser-induced breakdown spectroscopy system. The electron temperature and number density of Ge plasma are evaluated by using the Boltzmann plot and stark broadening methods, respectively. The variations in emission intensity, electron temperature ( T e ), and number density ( n e ) of Germanium plasma are explored at various fluences, with and without employment of the magnetic field. It is observed that the magnetic field is responsible for significant enhancement of both excitation temperature and number density at all fluences. It is revealed that an excitation temperature increases from T e, max, without B = 16, 190 to T e, max, with B = 20, 123 K. Similarly, the two times enhancement in the electron density is observed from n e, max, without B = 2 × 10 18 to n e, max, with B = 4 × 10 18 cm −3 . The overall enhancement in Ge plasma parameters in the presence of the magnetic field is attributed to the Joule heating effect and adiabatic compression. With increasing fluence both plasma parameters increase and achieve their maxima at a fluence of 12.8 J/cm 2 and then decrease. In order to correlate the plasma parameters with surface modification, scanning electron microscope analysis of irradiated Ge was performed. Droplets and cones are formed for both cases. However, the growth of ridges and distinctness of features is more pronounced in case of the absence of the magnetic field; whereas surface structures become more diffusive in the presence of the magnetic field.